2013
DOI: 10.1371/journal.pgen.1003087
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-Wide Association Study (PheWAS) for Detection of Pleiotropy within the Population Architecture using Genomics and Epidemiology (PAGE) Network

Abstract: Using a phenome-wide association study (PheWAS) approach, we comprehensively tested genetic variants for association with phenotypes available for 70,061 study participants in the Population Architecture using Genomics and Epidemiology (PAGE) network. Our aim was to better characterize the genetic architecture of complex traits and identify novel pleiotropic relationships. This PheWAS drew on five population-based studies representing four major racial/ethnic groups (European Americans (EA), African Americans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
151
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 37 publications
0
151
1
Order By: Relevance
“…Pleiotropy, defined here as one gene affecting more than one phenotype, has become increasingly important in interpreting both genotype-phenotype maps and underlying factors that affect comorbidity, and has been integrated into several methods for genome wide association studies (GWAS) (Chung et al 2014;Hill and Zhang 2012;Lee et al 2012;Li et al 2014a, b;Pendergrass et al 2013;Rzhetsky et al 2007;Sivakumaran et al 2011;Solovieff et al 2013;Stearns 2010;Wagner et al 2008;Wagner and Zhang 2011;Yang et al 2015). Studies of pleiotropy can impact our understanding of underlying disease processes, and implicitly, the prevention and treatment of disease as well as predicting adverse reactions to drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleiotropy, defined here as one gene affecting more than one phenotype, has become increasingly important in interpreting both genotype-phenotype maps and underlying factors that affect comorbidity, and has been integrated into several methods for genome wide association studies (GWAS) (Chung et al 2014;Hill and Zhang 2012;Lee et al 2012;Li et al 2014a, b;Pendergrass et al 2013;Rzhetsky et al 2007;Sivakumaran et al 2011;Solovieff et al 2013;Stearns 2010;Wagner et al 2008;Wagner and Zhang 2011;Yang et al 2015). Studies of pleiotropy can impact our understanding of underlying disease processes, and implicitly, the prevention and treatment of disease as well as predicting adverse reactions to drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized importance of pleiotropy in developing a comprehensive understanding of gene-disease relationships (Chung et al 2014;Hill and Zhang 2012;Lee et al 2012;Li et al 2014a, b;Pendergrass et al 2013;Rzhetsky Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00439-017-1854-z) contains supplementary material, which is available to authorized users. et al 2007;Sivakumaran et al 2011;Solovieff et al 2013;Stearns 2010;Wagner et al 2008;Wagner and Zhang 2011;Yang et al 2015), little has been done to investigate the relationship between pleiotropy and risk variation as measured by effect sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the National Human Genome Research Institute GWAS Catalog revealed extensive pleiotropy among the common variants associated with complex traits. Many such examples have since been replicated and annotated in traditional epidemiologic and contemporary clinical collections [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Another major source of phenotyping data is the electronic health record (44,45). The breadth of these data presents both challenges and opportunities (46).…”
Section: Opportunities On the Horizonmentioning
confidence: 99%